1994
DOI: 10.1080/08870449408407470
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of self-help and support groups for cancer patients: A Review

Abstract: Following the recognition of the psychological difficulties faced by cancer sufferers, there has been a rapid growth in forms of group help. There is a wide variety of types, and nomenclature is far from consistent. Evaluation studies are reviewed, and issues of potential harmfulness are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Unfortunately, that distinction may be lost on newcomers, particularly ones told for years by an alcoholic that they are the reason the alcoholic drinks. A review of self-help groups for cancer patients found their helpfulness may be compromised if members perceive their peers are doing better than they are (Hitch, Fielding, & Llewelyn, 1994). Al-Anon newcomers and those continuing to struggle with acceptance of an alcoholic's self-destruction may blame themselves for their failure to make adequate progress.…”
Section: Perpetuating Victimizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, that distinction may be lost on newcomers, particularly ones told for years by an alcoholic that they are the reason the alcoholic drinks. A review of self-help groups for cancer patients found their helpfulness may be compromised if members perceive their peers are doing better than they are (Hitch, Fielding, & Llewelyn, 1994). Al-Anon newcomers and those continuing to struggle with acceptance of an alcoholic's self-destruction may blame themselves for their failure to make adequate progress.…”
Section: Perpetuating Victimizationmentioning
confidence: 95%
“…As a result, those in most need of help may fail to identify with their peers. They may exit the group or remain and claim that everything is fine (Hitch et al, 1994).…”
Section: Perpetuating Victimizationmentioning
confidence: 99%
“…A number of researchers have observed gender differences in cancer support groups. Based primarily on research with breast and prostate cancer support groups, they have found that men in cancer support groups tend to value information and education over personal experience and emotion sharing, whereas women place more emphasis on precisely these dimensions (Bottomley, 1997;Coreil & Behal, 1999;Gray et al, 1996Gray et al, , 1997Hitch, Fielding, & Llewelyn, 1994;Steginga et al, 2001;Thaxton et al, 2005).…”
Section: Content Of Group Meetingsmentioning
confidence: 97%
“…van den Borne et al, 1986;Hitch et al, 1994). Self-help groups are 'formed by peers who have come together for mutual assistance in satisfying a common need' (Katz, 1976, p.265).…”
Section: Introductionmentioning
confidence: 97%